The educational use of Facebook: a phenomenological exploration of faculty members’ and students’ lived experiences - Kadirhan, Zafer; Yildirim, Soner (Frontiers in Education, 2025)
Social media has become a pervasive element of higher education; however, the experiences of faculty and students with its educational use remain underexplored. This study employed a transcendental phenomenological design to investigate the lived experiences of three faculty members and 12 students who used Facebook as a learning tool. Data were collected through in-depth, semi-structured interviews and analyzed using Moustakas’ transcendental phenomenological method, which allowed for the identification of the essence of participants’ experiences while minimizing researcher bias. Findings indicate that Facebook facilitates communication, supports collaborative learning, and provides flexible access to educational resources, enhancing academic engagement. Participants reported benefits, including immediate information sharing and interactive peer support. However, challenges were also noted, including privacy concerns, potential distractions, and the informal nature of interactions, which may affect structured learning. These findings suggest that while Facebook can supplement formal education meaningfully, it should not replace traditional instruction. The study offers practical guidance on balancing engagement, privacy, and curriculum integration, providing educators with insight into thoughtfully leveraging social media in higher education. By presenting both benefits and limitations, this research contributes to a nuanced understanding of Facebook’s educational role and informs strategies for its practical use.